2017
DOI: 10.1111/jwas.12397
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Parameters and Blood Cell Morphology of Male and FemaleSchizothorax (Racoma) davidi(Sauvage)

Abstract: The aim of this study was to obtain a basic knowledge of the hematology of Schizothorax (Racoma) davidi (Sauvage). The results showed that red blood cell and white blood cell counts as well as mean cellular hemoglobin concentration were significantly higher in females than in males, while mean cell volumes were significantly lower in females than in males. No significant differences were seen in other hematological parameters in relation with gender. Under light microscope, erythrocytes (mature and immature), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The ESR values in fishes depicted no significant difference between the sexes or seasons. ESR values of current study were similar to those found in S. davidi (Zhu et al, 2017). On average, the MCH values in fishes range from 30 to 100 pg, MCV values varies between 150 and 350 fL and MCHC in fishes range from 18 to 30 g/dL (Hrubec and Smith, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…The ESR values in fishes depicted no significant difference between the sexes or seasons. ESR values of current study were similar to those found in S. davidi (Zhu et al, 2017). On average, the MCH values in fishes range from 30 to 100 pg, MCV values varies between 150 and 350 fL and MCHC in fishes range from 18 to 30 g/dL (Hrubec and Smith, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…Blood samples were collected from a jugular vein in the morning with a 1 mL syringe and collected in a sterile tube containing EDTA anticoagulants. Blood hematology parameters such as hematocrit, hemoglobin, total erythrocytes, and total leukocytes were analyzed according to standard procedures (Zhu et al 2017).…”
Section: Measurement In the Lambmentioning
confidence: 99%
“…Tang et al (2015) measured that the number of red blood cells, haemoglobin content and haematocrit of female piebald naked carp ( Gymnocypris eckloni ) were significantly lower than those of male 315 . The number of red blood cells, the number of white blood cells and the amount of haemoglobin in female David's schizothoracin ( Schizothorax davidi ) were significantly higher than those in male 327 . In conclusion, there were sex differences in blood physiological and biochemical indexes in fish, but the indexes were high and low without regularity between females and males, and the size of indexes varied with fish species.…”
Section: Influencing Factors Of Fish Haematological Indexesmentioning
confidence: 99%